Alzheimer's beta-amyloid peptides compete for insulin binding to the insulin receptor - Xie, Ling; Helmerhorst, Erik; Plewright, Brian; Van Bronswijk, Wilhelm; Martins, R. (Society of Neuroscience, 2002)
The amyloid- (A) peptide is neurotoxic and associated with the pathology of Alzheimer's disease (AD). We investigated the effect of A peptides on insulin binding to the insulin receptor because it is known that (1) A and insulin are both amyloidogenic peptides sharing a common sequence recognition motif, (2) A and insulin are substrates for the same insulin degrading enzyme, and (3) impaired glucose metabolism is a characteristic event in the pathology of AD. We discovered that A1-40 and A1-42, the main physiological forms, reduced insulin binding and receptor autophosphorylation. The reduction in binding was caused by a decrease in the affinity of insulin binding to the insulin receptor. This reduction was independent of the receptor concentration. The reverse, control peptide A40-1 did not reduce insulin binding or insulin receptor autophosphorylation. These results demonstrate that A is a direct competitive inhibitor of insulin binding and action. We speculate that the increased levels of A in Alzheimer's disease may be linked to the associated insulin resistance that has been observed previously in this disease.